The Manifestation of Realism and Modernism Styles in Uzbek and English Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides a comparative analysis of the manifestation of realism and modernism as two prominent literary movements in Uzbek and English literature. The research explores how each movement emerged in its own historical and cultural context and how these global trends were interpreted and transformed within the literary traditions of both nations. In English literature, realism gained momentum in the 19th century as a response to Romanticism, focusing on everyday life, social dynamics, and the inner struggles of individuals. Authors such as Charles Dickens, George Eliot, and Thomas Hardy portrayed the realities of their time, addressing issues like poverty, class disparity, and moral dilemmas. Meanwhile, modernism in English literature, as represented by Virginia Woolf, James Joyce, and T. S. Eliot, reflected a radical shift in narrative form, language experimentation, and existential themes driven by the disillusionment of the early 20th century. The article then transitions to the Uzbek literary scene, where realism emerged more distinctly in the early 20th century, notably in the works of Abdulla Qodiriy, Cho‘lpon, and Fitrat, who depicted social change, colonial oppression, and the everyday struggles of the Uzbek people. Uzbek realism carried a strong ideological and reformative undertone, often merging national identity with literary expression. In contrast, modernism in Uzbek literature—though influenced by Soviet literary policies and local cultural realities—found a nuanced expression in post-independence narratives, with authors experimenting more boldly with form, fragmentation, and subjectivity. By analyzing selected texts from both literatures, the article highlights stylistic features such as character construction, narrative voice, linguistic choice, and thematic focus. It underscores how realism, rooted in objectivity and social documentation, contrasts with modernism’s introspective, fragmented, and experimental nature. The article also explores the cross-cultural transmission of literary ideas and how global movements are localized, adapted, or resisted within national literatures. It concludes that while the stylistic markers of realism and modernism may be similar across literatures, their function, evolution, and socio-political significance are deeply shaped by the cultural and historical environments in which they operate. This comparative approach offers insight into the shared human experience and diverse artistic responses captured through literature in two different yet intellectually connected worlds.